2004
DOI: 10.1111/j.1478-3231.2004.0894.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of tumor necrosis factor‐α correlate with severity of hepatic encephalopathy due to chronic liver failure

Abstract: Serum levels of TNF correlate positively with the severity of HE in patients with chronic liver failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 20 publications
(32 reference statements)
5
76
0
5
Order By: Relevance
“…IL-6 and TNF-α are also thought to be involved [14,31,32] and both are able to increase NOx levels. In our study there were no differences at all between the groups and also patients with bleeding had no difference in these cytokine levels compared to patients with other forms of decompensation.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 and TNF-α are also thought to be involved [14,31,32] and both are able to increase NOx levels. In our study there were no differences at all between the groups and also patients with bleeding had no difference in these cytokine levels compared to patients with other forms of decompensation.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a is a macrophage derived cytokine, produced in large amounts in response to endotoxin. High AF levels of this cytokine have been observed in our patients with SBP [11,16,17]. Since SBP is considered to be the consequence of repeated episodes of bacteremia following intestinal bacterial translocation with seeding of AF, it might be considered that the intermittent presence of bacteria in blood may be followed by an activation of the cytokine cascade [11].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, intestinal bacterial overgrowth and bacterial translocation are increased in cirrhosis [21] . Besides endotoxins, the other possible factors stimulating NO production include cytokines such as TNF-α, IL-1, IL-6, and IFN-γ [22][23][24] Among these, TNF-α has been studied the most. LopezTalavera et al found that anti-TNF-α antibody increases mean arterial pressure and systemic vascular resistance, and decreases cardiac index and portal pressure [25] .…”
Section: Endocannabinoidsmentioning
confidence: 99%